Cranial nerve involvement in varicella zoster virus after renal transplantation. Issue 4 (1st October 2020) - Fan, Jennifer Nielsen; Fan, Jerry; Ali, Hameed
Abstract: This case describes a 60-year-old immunosuppressed man after renal transplant who presented to the emergency department with 1 week of generalized weakness, a 20-lb unintentional weight loss, sore throat, dysarthria, dysphagia, cough, and shortness of breath. Additionally, he developed tinnitus, headaches, photophobia, and neck stiffness. He underwent an extensive workup including a lumbar puncture with meningitis and encephalitis panel, which was positive for varicella zoster virus. He never developed a dermatomal vesicular rash but had persistent dysphagia and aspiration and was eventually diagnosed with Vernet syndrome. This case highlights theories for the increase in varicella zoster virus encephalitis cases causing neurologic symptoms and proposes that this trend is likely to continue.